Alternate use of thrombopoietin receptor agonists in adult primary immune thrombocytopenia patients: A retrospective collaborative survey from Italian hematology centers. Issue 1 (9th November 2017) - Cantoni, Silvia; Carpenedo, Monica; Mazzucconi, Maria Gabriella; De Stefano, Valerio; Carrai, Valentina; Ruggeri, Marco; Specchia, Giorgina; Vianelli, Nicola; Pane, Fabrizio; Consoli, Ugo; Artoni, Andrea; Zaja, Francesco; et al.
Abstract: Sequential use of the TPO‐RAs romiplostim and eltrombopag in ITP patients failing either agent was retrospectively evaluated to assess efficacy and impact of clinical characteristics on outcome. Patients were grouped into 5 categories: efficacy issues : 1 st TPO‐RA failure; loss of response; non‐efficacy issues : platelet fluctuations; patient's preference; adverse event development. Either one TPO‐RA sequence was analyzed at 3 month and at last follow‐up. 106/546 patients on TPO‐RA underwent switch and 65% achieved, regained or maintained a short‐ term response independent of switch sequence, gender or age; lower response rates were associated with lines of previous therapy; disease duration lowers probability to respond. Clinically, patients switched for efficacy issue did not differ from those switched for non‐efficacy issues. Response was achieved/regained in 57.8% of patients switched for efficacy issues, the lowest response rates were observed in non‐responders to 1 st TPO‐RA; 80% of patients switched for non‐efficacy issues maintained a response. Platelet fluctuation resolved in 44.4%. Of the 49 patients evaluable for long‐term outcome, 27 were in response on therapy; 16 discontinued the TPO‐RA for reasons other than efficacy, while only 6 were non responders. We confirm the efficacy of TPO‐RA switch; once achieved, response to the 2 nd TPO‐RA seems durable.